GRAMMATICAL ERRORS COMMITED BY EIGHT GRADE STUDENTS IN WRITING RECOUNT TEXT - Fridayanthi, N.P.T.M.E. (International Journal of Language and Literature, 2017)
There are 2 purposes of conducting this study, (1) finding the errors commonly made in writing recount text by eighth grades students at SMPN 2 Seririt; and (2) finding the sources of the errors committed in writing recount text by eighth grades students at SMPN 2 Seririt. As a descriptive qualitative research, there were two main instruments used in this study, they were  the researcher and the sample of writing. After gaining the data, then descriptive analysis was conducted. From 30 students’ writing which were analyzed based on surface strategy taxonomy proposed by Dulay et al. (1982), it is found that there are 169 errors committed by the subject including 130 (77%) omission errors, 14 (8.28%) misordering errors, 13 (7.7%) misformation errors, and 12 (7.1%) addition errors. Omission error becomes the most frequent errors committed by the students. There are three types of errors sources found in this study, those are intralingual transfer (90.96%), interlingual transfer (7.22%), and context of learning (1.8%).